SEKOLAH DEMOKRATIS - Tabitha Lopulalan (TANGKOLEH PUTAI, 2020)
In this globalization era, every country is competing to increase HDI. This is considered as an important thing, because HDI is a capital to carry out any development program in a system. Indonesia, as one of the most populous countries in the world, whether you want it or not, is currently in the flow of competition. In accordance with the results of research from researchers from the field of science that is the focus of their study, it turns out that the education sector is a system that determines the quality of the Human Development Index (HDI). This means, it is time for Indonesia to reform the education system from all levels. All components involved in the education process must be reformed. Some of the components that have received attention are the school and curriculum. These two components were reformed, so that an increase in the HDI of the Indonesian nation could be realized. One aspect of educational reform is democracy. Schools as educational institutions must implement democratic education. This must be proven through the curriculum applied in schools. So that education can answer the needs of the job market as a capital to improve the welfare of the Indonesian people, towards a just and prosperous society based on the 1945 Constitution.